Recognition histological grade of malignancy in ovarian adenocarcinoma - Taylor, Howard (2015)
The author briefly reviews the principles on which the histological tumor classification technique is based according to their degree of malignancy, which is useful to the clinic to establish a system based on the correlation has been established between the histological grading of malignancy grade and prognosis the further clinical course of malignant ovarian tumors. From a biochemical standpoint, the tissue microespectrofotométrica content determination DNA (deoxyribonucleic acid) and mediation of nucleolar diameter as expression of tissue content of RNA (ribonucleic acid), correlate well with the degree of malignancy established with histological techniques and traditional cytology.